Mammary Analogue Secretory Carcinoma of the Palate: Case Report and Review of the Literature - Christian Boliere; James Murphy; Mohammed Qaisi; Frances Manosca; Henry Fung (Case Reports in Dentistry)
Mammary analogue secretory carcinoma (MASC) is a recently described salivary gland tumor, with a limited number of published reports. Less than three hundred cases have been reported in the literature and only 18 of these cases have been reported in minor palatal salivary glands, though publication bias is likely a factor. We present a case of a 57-year-old male who was diagnosed with MASC tumor presenting in a minor salivary gland and briefly review the current literature. MASC has a variety of histological features and different range of clinical behaviors. The histopathological diagnosis of MASC can be difficult, and the immunohistochemical profile of MASC is still being updated. The gold standard for MASC diagnosis is cytogenetics, with the majority having a translocation t(12;15)(p133;q25). Presently, there is no conclusive evidence that MASC should be treated differently than any other low-grade malignant salivary gland tumors, though high-grade transformation has been described.